Actividad alexítera de los extractos de costus pulverulentus C. Presi Desmodium adscendens (Sw.) DC., Begonia glabra Aubl., sobre el veneno de Bothrops asper (Equis) - Granda Calle, Nelly Geovanna (2015)
Ethno-medicinal knowledge is very rich in our country; vegetal species as Costus pulverulentus C. Presl, Desmodium adscendens (Sw.) DC., and Begonia glabra Aubl have been used for poisonous snakebites treatment, as those caused by Bothrops asper (equis) the most common ophidian species in Ecuador. If someone or something decided to disturbed, this snake has a violent and difficult to predict behavior, and is considered responsible for most attacks in the country, becoming a public health problem since the time it takes to attend an affected patient can make the difference between necrosis development, amputation or death. The present study was conducted in order to verify the alexítera activity of extracts of Costus pulverulentus C. Presl, Desmodium adscendens (Sw.) DC., and Begonia glabra Aubl, on Bothrops asper poison. Samples were taken at Km 113 of the Calacalí - Puerto Quito road and at Mindo, and were transported to the laboratories of the Universidad Politécnica Salesiana (Salesian Polytechnic University) to determine their neutralizing capacity on the hemolysis caused by the poison of these serpents, which was obtained from specimens of three different areas of the Ecuadorian geography. It was found that alcoholic extracts of these species have more alexítera activity in a concentration ratio of 1:20 (poison:extract) than the standard used (Equisetum bogotense); that the alexítera activity Begonia glabra Aubl., is higher on the poison from specimens of the coastal region; and also that Desmodium adscendes (Sw.) DC., has higher activity on the poison of specimens taken of the province of Bolivar.